"Lifestyle" élelmiszerek: az európai szabályozás - Balogh, Sándor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The paper describes the significant consumer benefíts of lifestyle products, növel foods and new foods and food ingredients belonging to the group of botanicals. Their specificity is that these foods can be marketed in Europe after a strici regulatory procedure, and they are added to the list of authorized products by the European Food Safety Authority upon the initiation of national food safety authorities following extensive harmonization with Member States.